2020
DOI: 10.1521/bumc_2020_84_04
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-compulsive symptom profiles in individuals exposed to interpersonal versus noninterpersonal trauma

Abstract: Ojserkis et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 81 publications
1
4
0
Order By: Relevance
“…"Age regression" is a cognitiveperceptual suggestion which induces people to go back and re-experience their earlier periods of life, and only the upper 10-15% high hypnotizable individuals have passed this item [46]. The predictions on two PERM styles indicated that even in healthy people, high accessibility to unpleasant memories in childhood contributes to the maladaptation in current life, including a lowed desire in interpersonal relationships, and a sense of losing control and compulsive tendency, which is in line with previous report on individuals with trauma experience [47]. The positive correlation between "arm immobilization" and histrionic style as well as the positive predictions of "age regression" and "arm immobilization" on histrionic style in healthy volunteers are supported by the social role-taking theory [48] which proposes the correlation between subjective identification, active attempts to achieve social role construction, and the feeling "like being hypnotized".…”
Section: Discussionsupporting
confidence: 88%
“…"Age regression" is a cognitiveperceptual suggestion which induces people to go back and re-experience their earlier periods of life, and only the upper 10-15% high hypnotizable individuals have passed this item [46]. The predictions on two PERM styles indicated that even in healthy people, high accessibility to unpleasant memories in childhood contributes to the maladaptation in current life, including a lowed desire in interpersonal relationships, and a sense of losing control and compulsive tendency, which is in line with previous report on individuals with trauma experience [47]. The positive correlation between "arm immobilization" and histrionic style as well as the positive predictions of "age regression" and "arm immobilization" on histrionic style in healthy volunteers are supported by the social role-taking theory [48] which proposes the correlation between subjective identification, active attempts to achieve social role construction, and the feeling "like being hypnotized".…”
Section: Discussionsupporting
confidence: 88%
“…In particular, the association between trauma exposure and OCD is much stronger for compulsions than obsessions, suggesting that compulsions are sometimes used to cope with trauma and trauma-related symptoms (Miller & Brock; Pinciotti & Fisher, 2022). A growing body of literature suggests relationships between OCD and childhood or adulthood interpersonal traumas (Barzilay et al, 2019; Boger et al, 2020; Miller & Brock, 2017; Ojserkis et al, 2020), indirectly experienced events (Pinciotti, Riemann, & Wetterneck, 2021), and certain OCD symptom themes (e.g., doubting, harm/sex/scrupulosity, contamination, hoarding/saving, symmetry, repeating, checking, collecting/saving, and ordering/arranging [Cromer et al, 2007; Fontenelle et al, 2012; Pinciotti & Fisher, 2022]). Case Example: AN sought concurrent OCD and PTSD treatment to work through symptoms of pathological doubt, just right, over-explaining, and hesitating following a history of extensive childhood abuse. She described an upbringing in which she was physically punished by her father for minor indiscretions and was manipulated into believing she was responsible for her father’s abusive behavior and unpredictable mood states.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…In particular, the association between trauma exposure and OCD is much stronger for compulsions than obsessions, suggesting that compulsions are sometimes used to cope with trauma and trauma-related symptoms (Miller & Brock;Pinciotti & Fisher, 2022). A growing body of literature suggests relationships between OCD and childhood or adulthood interpersonal traumas (Barzilay et al, 2019;Boger et al, 2020;Miller & Brock, 2017;Ojserkis et al, 2020), indirectly experienced events , and certain OCD symptom themes (e.g., doubting, harm/sex/scrupulosity, contamination, hoarding/saving, symmetry, repeating, checking, collecting/saving, and ordering/arranging [Cromer et al, 2007;Fontenelle et al, 2012;Pinciotti & Fisher, 2022]).…”
Section: Conceptualizing the Comorbiditymentioning
confidence: 99%
“…Several other studies have examined relationships between trauma type and MC, with consistent support for a link between sexual trauma and MC. Ojserkis et al (2020) found that survivors of interpersonal traumas (e.g., sexual or physical violence) reported higher levels of MC compared to survivors of noninterpersonal traumas (e.g., motor vehicle accidents). Berman et al (2012) found that exposure to childhood trauma was associated with MC in a large sample of undergraduate students.…”
Section: The Relationship Between Trauma and MCmentioning
confidence: 94%